Cis-acting elements involved in the transcriptional control of the glucoamylase and mucin genes of Saccharomyces cerevisiae - Gagiano, Marco (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 1998.